L’ibadisme maghrébin en contexte fatimide (début xe-milieu xie siècle) - Cyrille Aillet (Revue des Mondes Musulmans et de la Méditerranée)
In Ibadi sources, the advent of the Fatimids has fuelled a memory of the Fall, the aspects of which we will examine. This vision is completed by the apologetical narrative of resistance against the “tyrants”. But how could the Ibadi orthodoxy compete with the heroic saga of Abū Yazīd, the schismatic figurehead of rebellion? First, by presenting him as a “Kharijite” leader who had spread the “fitna” over the whole country, and secondly by putting forward another revolt. The forgotten episode of Bāghāya (969) was seen as a legitimate and righteous uprisal, decided by the community and lead by its ulama. But this attempt to produce a counter-memory also sheds light on another reality: the coexistence between the Ismaili authority and the Ibadi-Wahbi community, represented by its religious elite.